2022
DOI: 10.3389/fnbeh.2022.1078983
|View full text |Cite
|
Sign up to set email alerts
|

Impact of specific serotonin receptor modulation on restricted repetitive behaviors

Abstract: Restricted, repetitive behaviors (RRBs) are commonly divided into two behavioral categories, lower-order and higher-order RRBs. Individuals displaying lower-order motoric RRBs may express repetitive hand flapping behaviors, body rocking back and forth movements, and continuous body spinning. Higher-order RRBs most commonly cover the behavior inflexibility and cognitive rigidity commonly found in disorders such as autism spectrum disorder and obsessive-compulsive disorder. Various neuropsychiatric disorders are… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 92 publications
0
4
0
Order By: Relevance
“…Despite this link between 5-HT activity and locomotion in the hippocampus, it remains puzzling that the EMG signal, which reflects spontaneous and irregular movement, was observed in our data to be consistently coupled to the infraslow 5-HT oscillation. While the literature linking 5-HT and repetitive movements could shed more light on the question (51,52), further studies examining the link between hippocampal 5-HT and movement are required to clarify this relationship.…”
Section: Discussionmentioning
confidence: 99%
“…Despite this link between 5-HT activity and locomotion in the hippocampus, it remains puzzling that the EMG signal, which reflects spontaneous and irregular movement, was observed in our data to be consistently coupled to the infraslow 5-HT oscillation. While the literature linking 5-HT and repetitive movements could shed more light on the question (51,52), further studies examining the link between hippocampal 5-HT and movement are required to clarify this relationship.…”
Section: Discussionmentioning
confidence: 99%
“…This inhibition of dopamine release by CB2 receptors helps regulate motor movements and reduce the frequency of repetitive behaviors. Activation of 5-HT receptors, specifically 5-HT2A/2C receptors, can induce repetitive behaviors [ 249 ]. Loss of functional CB2 receptors leads to increased repetitive behaviors following 5-HT2A/2C receptor activation, suggesting a regulatory role for CB2 receptors in this process [ 250 ].…”
Section: Neurological Disorders and Cannabis Studiesmentioning
confidence: 99%
“…ASD is a complex neurodevelopmental and neuropsychiatric disorder characterized by deficits in social communication and the manifestation of restricted/repetitive behaviors . ASD is intricately linked to impairments of neurogenesis, synaptic pruning, and synaptic plasticity. ASD is often accompanied by secondary disorders such as seizure, depression, anxiety, and hyperactivity. Diagnosing and treating ASD pose substantial challenges due to heterogeneity of symptoms, varying degrees of severity, comorbidity, and incomplete understanding of etiology. ASD arises from a complex interplay of genetic and environmental factors, including epigenetic factors, gene polymorphism, viral infections, metabolic dysfunction, and dysfunction of neurotransmitters in the brain, such as serotonin, glutamate, and acetylcholine. , Studies of neurotransmitter dysfunction in the context of ASD have been consistently reported, and among these, the modulation of serotonin receptors has emerged as a factor associated with social deficits and repetitive behaviors. , …”
Section: Introductionmentioning
confidence: 99%